Collaborative design methodologies and social dynamics: a portuguese social and public health case study - Bernarda, João Nuno Gago (2021)
This research project addresses the understanding of collaborative action among disciplines from distinct branches of science with particular focus on social action. It also aims to evaluate the impact of this collaborative action on responding to the needs of different highly vulnerable communities and on other participants of these same processes. The integration of design in the social sector is a growing tendency, albeit to a certain extent characterised by novelty and resistance. Hence, and within this framework, the present thesis seeks to respond to the hypothesis “Collaborative design methodologies improve the effectiveness of social services’ practice”, and is organized into six phases, namely: the theoretical framework and the main research question, the construction of the model structure of the research and identification of the hypothesis, a review of the collaborative models and Social Design framework through case studies, the application of an in-depth case, the collection, processing and analysis of data and conclusions. The aim of this research is to ascertain the influence of Design on collaborative action, namely in the generation of more effective results and in obtaining information, and its impact on other sectors (intervention, assistance, solidarity, community action and social development). Moreover, it has served to highlight the potential for future alliances with prospective partners who, in light of the developed process, have manifested an interest in establishing co-partnerships of this nature. This study sheds light upon the potential of integrating Design and Designers in organizations in general, and in particular in those that aim to respond to the needs of communities who are most exposed to social impacts. By increasing the capacity to respond to their vulnerabilities, the risk of social exclusion and isolation will be significantly reduced. Additionally, awareness on the part of social partners, of the added value of Design and its contribution to the maturity and sustainability of social processes will be enhanced.